Implementasi Nilai-Nilai Etika Organisasi Dalam Meningkatkan Kinerja dan Pendewasaan Berorganisasi di HIQMA UIN Syarif Hidayatullah Jakarta - M. Reza Saputra (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2025)
This research aims to analyze the implementation of organizational ethical values in improving performance and organizational maturity at HIQMA UIN Syarif Hidayatullah Jakarta, focusing on word patterns, thought patterns, and attitude patterns in organizational dynamics. The research employs a qualitative approach with a case study method. Data was collected through direct observation, in-depth interviews with HIQMA administrators and members, and organizational document analysis. Informants were selected through purposive sampling, and data were analyzed using thematic analysis techniques with validation through data source triangulation. The implementation of organizational ethical values at HIQMA shows positive impacts on three main aspects: (1) increased leadership effectiveness and management performance, (2) strengthening organizational culture through the integration of Islamic values, and (3) development of member professionalism through comprehensive training programs such as Management Upgrading. This research provides a new perspective on integrating Islamic ethical values in student organization development, particularly in organizations focusing on Quranic talent development and Islamic arts. The research results provide a practical framework for student organizations to implement ethical values to improve performance and organizational maturity, including management capacity development strategies and monitoring evaluation systems.